Mitochondrial quality control in stroke: From the mechanisms to therapeutic potentials. Issue 4 (17th January 2022) - Tian, Heyan; Chen, Xiangyu; Liao, Jun; Yang, Tong; Cheng, Shaowu; Mei, Zhigang; Ge, Jinwen
Abstract: Mitochondrial damage is a critical contributor to stroke‐induced injury, and mitochondrial quality control (MQC) is the cornerstone of restoring mitochondrial homeostasis and plays an indispensable role in alleviating pathological process of stroke. Mitochondria quality control promotes neuronal survival via various adaptive responses for preserving mitochondria structure, morphology, quantity and function. The processes of mitochondrial fission and fusion allow for damaged mitochondria to be segregated and facilitate the equilibration of mitochondrial components such as DNA, proteins and metabolites. The process of mitophagy is responsible for the degradation and recycling of damaged mitochondria. This review aims to offer a synopsis of the molecular mechanisms involved in MQC for recapitulating our current understanding of the complex role that MQC plays in the progression of stroke. Speculating on the prospect that targeted manipulation of MQC mechanisms may be exploited for the rationale design of novel therapeutic interventions in the ischaemic stroke and haemorrhagic stroke. In the review, we highlight the potential of MQC as therapeutic targets for stroke treatment and provide valuable insights for clinical strategies.